Differential protein–protein interactions of full length human FasL and FasL fragments generated by proteolysis - Lettau, Marcus; Voss, Matthias; Ebsen, Henriette; Kabelitz, Dieter; Janssen, Ottmar (Experimental cell research, 2014)
Fas ligand (FasL) is a death factor of the tumor necrosis factor superfamily. Like other members of this family of type II transmembrane proteins, FasL is subject to ectodomain shedding by a disintegrin and metalloproteinases (ADAMs) liberating soluble FasL and leaving membrane-integral N-terminal fragments (NTFs). These NTFs are further processed by intramembrane proteolysis through signal peptide peptidase-like 2a (SPPL2a), releasing intracellular domains (ICDs) which might translocate to the nucleus to regulate transcription. Previous work established that the proline-rich domain within the cytosolic N-terminus of FasL is required for protein–protein interactions with different Src homology 3 (SH3) or WW domain proteins. Distinct binding partners regulate FasL storage and surface appearance or are involved in other aspects of FasL biology. Given the large number of FasL interactors, we asked whether proteolytically processed FasL fragments associate with the same or distinct sets of SH3 domain proteins. To address this, we performed co-precipitation experiments using a monoclonal antibody directed against the FasL N-terminus for subsequent protein detection of full length FasL and NTFs/ICDs in Western blots. We demonstrate that members of the sorting nexin (SNX) family bind full length FasL and its N-terminal fragments whereas members of the Pombe Cdc15 homology (PCH) protein family bind full length FasL, but fail to associate with processed FasL. Thus, we provide first evidence that full length FasL and FasL fragments display selectivity regarding their association with intracellular binding partners. The differential binding most likely governs the fate and function of the intracellular FasL fragments. •Proteolytic processing of FasL can be visualized using the newly established mab Fc2.•FasL fragments are constitutively produced in transfectants and inducible in T cells.•PCH proteins and sorting nexins were analyzed as known FasL interactors.•Sorting nexins co-precipitate full length FasL and its N-terminal fragments.•PCH proteins bind full length FasL but do not co-precipitate N-terminal fragments.